At-Ṭarāiq an-Nājiḥah fī Taʻlīm Mahārah al-Kalām fi Lugah al-ʻArabiyyah - Ahmad Mizan Rosyadi Abdul Jalil Manan; Nor Holis Bin Nafsah (INAIFAS PRESS, 2021)
Learning Arabic-speaking skills is a must for Arabic learners. Several methods are often practiced in learning to speak Arabic. Educators need to pay attention to the typology of their students so that they can choose the right method. This research-oriented was to evaluate the relevant methods for studying Arabic communication. In this article, the researcher used a qualitative method with data sources from the literature documentation. The results of this research found that there were advantages and disadvantages to each method that was used to train students' speaking skills. Success in using the method depended on the competence of educators in applying it, supporting media, and teaching materials that were appropriate to the context of the learner. To achieve Arabic-speaking skills, a combination of various elements in learning is needed.